Formulation and Evaluation of Acalypha Indica Phytosomal Herbal Gel - Jasmimol.K; Dr.C. Rubina Reichal; P. Saminathan; S.Manju (International Journal of Pharma and Bio Sciences, 2023)
The current work aimed to formulate an Acalypha indica as a phytosomal herbal gel that can be used for antimicrobial activity and enhance the therapeutic effect. Phytosomes are vesicular drug delivery systems when incorporated with phytoconstituents of plant extracts into phospholipids to form lipid molecular complexes. Phytosome drug delivery has provided good absorption i.e polar biomolecules, then conventional herbal extracts. Ten formulations of phytosomal complex were prepared using an extract of Acalypha indica with varying proportions of Cholesterol and Lecithin. All phytosomal formulations were evaluated for percentage of yield, Entrapment efficiency, Drug content, in vitro drug release studies and SEM. The optimized formulation was selected based on the in vitro study, in this formulation, 3(F3) showed the maximum percentage of drug release, and it was converted into the gel using carbopol 934P as a gelling polymer. The developed gel was studied for various evaluation parameters like homogeneity, pH, Rheological study, spreadability and Extrudability. The optimized formulation 3(F3) showed excellent antibacterial activity. The antibacterial activities of Acalypha indica formulation against the microorganisms were examined and compared with gentamycin as a reference. The results showed that the formulation was effective against bacteria. The release kinetic study result revealed the formulation followed by the Non-Fickian diffusion mechanism. Stability studies were conducted per ICH guidelines, and no change occurred during the duration of the stability study. From this, it can be concluded that topical delivery is used for localized effect at the site of their application and the phytosomal delivery techniques minimize the toxicities and improve the absorption and bioavailability and showed good penetration into the skin for antibacterial activity.